EFL Teachers' Evaluation on “Skillful-Teaching Writing and Reading 02" - Le, Thao; Le, Mai; Nguyen, Quyen (FOSTER: Journal of English Language Teaching, 2021)
In case that many reforms in learning and teaching English in Vietnam were implemented, exploring the effectiveness of different coursebooks was raised to be a sufficient need. This research is more qualitative than quantitative in its nature, aiming to investigate EFL teachers’ evaluation of the coursebook Skillful – Reading & Writing 02 in a specific educational institution in the Mekong Delta. Thirteen teacher participants using the books were invited to participate in this study. Quantitative and qualitative data were collected by using two instruments, questionnaires and semi-interviews. The study provided a new checklist for evaluating materials in teaching and learning reading and writing. The findings showed that (1) the merits of the coursebook Skillful – Reading & Writing 02: e.g. colorful illustrations, numerous online learning resources accompanying online accounts, suggestive topics, updated contents, and impressive study skills component; and (2) demerits of the book in terms of writing section which does not match the general objectives of the program. Likewise, (3) the cons are regarding quite small font size and long listening activities of the coursebook. Additionally, some implications were suggested in this study to enhance the effectiveness of using sufficient materials for higher educational institutions.